Pendidikan Agama Kristen dalam Sudut Pandang John Dewey - Marthen Sahertian (JURNAL TERUNA BHAKTI, 2019)
John Dewey was a philosopher and an American educator, offering participatory educational patterns bring learners to be able to deal directly with the reality in their environment, so that learners can integrate the material that he had learned in class with the existing reality. John Dewey's educational thought can be applied to Christian education in local churches ranging from children's Christian education, Christian education adolescent / youth and Christian education of adults and the elderly. At the end of the learning process every believer acquire knowledge of the truth of God's word sehinggamampu solve problems and apply what has been learned. Abstrak John Dewey adalah seorang filsuf dan tokoh pendidikan berkebangsaan Amerika Serikat, menawarkan pola pendidikan partisipatif membawa peserta didik untuk mampu berhadapan secara langsung dengan realita yang ada di lingkungannya, sehingga peserta didik dapat mengintegrasikan antara materi yang ia pelajari di kelas dengan realita yang ada. Pemikiran pendidikan John Dewey dapat diterapkan pada Pendidikan Agama Kristen (PAK) dalam gereja lokal mulai dari PAK anak, PAK remaja/pemuda dan PAK orang dewasa dan lansia. Pada akhir proses pembelajaran setiap orang percaya memperoleh pengetahuan kebenaran firman Tuhan sehinggamampu menyelesaikan masalah dan mempraktekkan apa yang telah dipelajari.